The Impact of Green Recruitment and Employee Empowerment on Organizational Culture and SDGs Achievement - Damayant, Wiwit; Budiyono, Eko; Sumardi, Sumardi; Latuconsina, Abdul Samad; Pahala, Yosi (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of green recruitment and employee empowerment on the achievement of the Sustainable Development Goals (SDGs), with organizational culture serving as a mediating variable in companies in Indonesia. This research is grounded in Green Human Resource Management (GHRM) theory and organizational culture theory, which emphasize that green recruitment as an entry point and employee empowerment as a behavioral mechanism can strengthen the internalization of sustainability values within organizations. Organizational culture is viewed as a crucial bridge linking green HR policies to employees’ pro-environmental behavior and the company’s SDG achievements. The study employs a quantitative approach with an explanatory survey design. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) based on responses from 100 participants representing various company sectors in Indonesia that published Sustainability Reports for the 2023–2024 period. The research instrument was developed by adapting indicators from the GHRM, empowerment, organizational culture, and SDG literature. Validity, reliability, and goodness-of-fit tests were conducted to ensure the quality of the model. The findings reveal that green recruitment and employee empowerment significantly influence green organizational culture, while employee empowerment has the strongest direct effect on SDG achievement. Organizational culture is proven to mediate the relationship between green recruitment and employee empowerment and the achievement of SDGs. Practically, these findings highlight that corporate success in supporting the SDGs depends not only on administrative compliance, such as sustainability reporting, but also on transforming norms, values, and daily decision-making at the employee level. This study contributes practical insights for developing HR metrics directly linked to SDG indicators and supports policy transformation toward a green economy in Indonesia.